Building plan approval process / Nur Azreen Mohd Zurab - Mohd Zurab, Nur Azreen (Universiti Teknologi MARA UiTM,Perak, 2022)
Generally this report explain the process of building plan approval and the procedure that needed in plan approval process. The plan does not involve all departments in MPKB because each department has its own responsibilities and roles. The purpose from this report to show how the process to get plan approval by following all the specification that already prescribed in law until get CCC form which mean the house available to stay. The objective of this report is show the procedure to get plan approval from involved department, the problem and the solution to solve during the plan approval process. This report also come with the objective of imposed charge during the process happened. To illustrate the appropriate methodology in the building approval plan is to follow all the rules laid down by the building laws. This report will explain all the step on how get approval plan and all the factor could be the problem when the process and the proper way to overcome the problem related and also the 3 imposed charge need to pay from client.